Teaching English pronunciation to multi-dialect first language learners: The revival of the Lingua Franca Core (LFC). (November 2018) - Zoghbor, Wafa Shahada
Abstract: The global spread of English as the world lingua franca has an impact on the goals of teaching pronunciation, where 'comfortable intelligibility' should be the goal rather than native-like pronunciation.Jenkins (2000) proposed the Lingua Franca Core (LFC), a syllabus that includes a list of phonological features that are, arguably, the minimum required to result in intelligible communication among non-native speakers of English (NNSs). This study has rethought the contents of this list for Arab learners. To this end, the intelligibility of 50 L1 Arabic learners of English at post-secondary level was evaluated by 18 non-Arab speakers using the buzzer technique, and an index has been developed for unintelligible utterances in the speakers' speech samples. The findings support most of the core features in the LFC except for the quality of the long vowel /ɜː/, rhotic /r/, and word stress in words of more than two syllables. These findings are used to propose a revised version of the LFC syllabus for Arab learners.